CHALLENGES IN TEACHING THE CREATION OF UZBEK FOLK MUSIC TO YOUNG PEOPLE (American Journal of Research in Humanities and Social Sciences, 2024)
Uzbek folk music, with its rich cultural heritage and unique musical traditions, plays a vital role in the cultural identity of Uzbekistan. Teaching the creation of Uzbek folk music to young people is crucial for preserving this musical heritage and ensuring its continuity. However, this endeavor is not without its challenges. This scientific article examines the problems associated with teaching the creation of Uzbek folk music to young people, including limited access to authentic resources, evolving societal values, and the need for innovative educational approaches. It highlights the importance of addressing these challenges to encourage the engagement and participation of young learners in the creation and preservation of Uzbek folk music.